Traditional measures of normal anal sphincter function using high‐resolution anorectal manometry (HRAM) in 115 healthy volunteers - Carrington, E. V.; Brokjær, A.; Craven, H.; Zarate, N.; Horrocks, E. J.; Palit, S.; Jackson, W.; Duthie, G. S.; Knowles, C. H.; Lunniss, P. J.; Scott, S. M. (Neurogastroenterology and motility, 2014)
Background High‐resolution anorectal manometry (HRAM) is a relatively new method for collection and interpretation of data relevant to sphincteric function, and for the first time allows a global appreciation of the anorectum as a functional unit. Historically, traditional anal manometry has been plagued by lack of standardization and healthy volunteer data of variable quality. The aims of this study were: (i) to obtain normative data sets for traditional measures of anorectal function using HRAM in healthy subjects and; (ii) to qualitatively describe novel physiological phenomena, which may be of future relevance when this method is applied to patients. Methods 115 healthy subjects (96 female) underwent HRAM using a 10 channel, 12F solid‐state catheter. Measurements were performed during rest, squeeze, cough, and simulated defecation (push). Data were displayed as color contour plots and analysed using a commercially available manometric system (Solar GI HRM v9.1, Medical Measurement Systems). Associations between age, gender and parity were subsequently explored. Key Results HRAM color contour plots provided clear delineation of the high‐pressure zone within the anal canal and showed recruitment during maneuvers that altered intra‐anal pressures. Automated analysis produced quantitative data, which have been presented on the basis of gender and parity due to the effect of these covariates on some sphincter functions. In line with traditional manometry, some age and gender differences were seen. Males had a greater functional anal canal length and anal pressures during the cough maneuver. Parity in females was associated with reduced squeeze increments. Conclusions & Inferences The study provides a large healthy volunteer dataset and parameters of traditional measures of anorectal function. A number of novel phenomena are appreciated, the significance of which will require further analysis and comparisons with patient populations. Two images of the same push in the same individual. Inspection of image (A) shows an increase in both anal and rectal pressures during push (which could led to the mistaken interpretation of dyssynergia) however, when the same event is displayed relative to rectal pressure (B), this more clearly reveals an appropriate change in the recto‐anal gradient.